Editorial for Special Issue "Antibacterial Resistance and Novel Strategies to Eradicate Bacterial Biofilms" - Theerthankar Das (MDPI AG, 2022)
Bacterial resistance to antimicrobial agents, including antibiotics, disinfectants, and detergents, is on the rise, with consequences associated with morbidity, mortality, and economic loss in the healthcare sector [...]